Analisis faktor-faktor yang mempengaruhi audit delay pada perusahaan property and real estate yang terdaftar di bei tahun 2009-2011 - Pricelly Erda Muharly; Hardi '; Julita ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study is to examine the effect of firm size, profitability, solvability,size of public accountant firm, and auditor’s opinion in property and real estate company that listed on indonesia stocks exchange for the a period 2009-2011. This study used is purposive sampling method and 28 firms were selected of a sample. Multiple regression analysis by SPSS 17 was used to testthe hypothesis proposed. The results of analyze showed that independent variables affect dependen variable on 36,3 %. And from the test results it can be concluded that firm size significantly. Profitability is not significantly, solvability is not significantly, size of public accountant firm sicnificantly and auditor’s opinion significantly influence audit delay during the period of this study. Keyword : audit delay, firm size, profitability, solvability, size of public accountant firm, and audit opinion.